The Role Of Evidence In Proving Cases Of Sexual Violence Against Women Based On Article 184 Of The Kuhap - Nur Aini Sandyta Br Tarigan; Muhammad Arif Sahlepi; Andry Syafrizal Tanjung (Fakultas Hukum Dehasen, 2026)
Legal protection in social life is crucial to protect people from violations of norms. Legal norms are needed in cases of sexual violence, encompassing various forms of physical, psychological, sexual, or economic suffering. Cases of violence against women are a topic of criminal procedure, particularly in the evidentiary process. Violence against women often faces evidentiary challenges due to the hidden nature of the crime, and victims often find it difficult to provide direct evidence. Collecting and presenting evidence in cases of violence against women faces various complex challenges. One of the main challenges is the often personal nature of the violence, making it difficult to obtain objective evidence. Another factor is that victims of violence often experience profound psychological trauma, which also affects the consistency or completeness of their testimony before investigators or the court. Shame, fear of social stigma, or threats from the perpetrator often make victims reluctant to report the incident. These obstacles require the involvement of experts from the National Commission on Violence Against Women (Komnas Perempuan), as well as legal services and assistance. Standard proof in cases of violence against women prioritizes the integration of various forms of evidence in accordance with Article 184 of the Criminal Procedure Code.